Global MicroRNA Expression Profiling Identifies Unique MicroRNA Pattern of Radioresistant Glioblastoma Cells - Ondracek, Jakub; Fadrus, Pavel; Sana, Jiri; Besse, Andrej; Loja, Tomas; Vecera, Marek; Radova, Lenka; Smrcka, Martin; Slampa, Pavel; Slaby, Ondrej (Anticancer research, 2017)
Glioblastoma multiforme (GBM) is the most aggressive intracranial tumor characterized with infaust prognosis. Despite advances in neurosurgical and radiotherapeutic techniques and chemotherapy, the median overall survival ranges between 12-15 months from diagnosis. The main cause of treatment failure is considered the presence of tumor cells resistant to conventional therapy, mainly radiotherapy. MicroRNAs (miRNAs) are small, non-coding RNAs that function as post-transcriptional regulators of gene expression and have been repeatedly proven to play important roles in pathogenesis and biological features of many cancers, including GBM and its radioresistant phenotype. In our study, we established radioresistant cells from the commonly used human GBM cell lines T98G, U87MG and U251. Consequently, we performed global miRNA expression profiling in both radioresistant and parental cell lines and identified 113 miRNAs with significantly different expression (p<0.05) between these two groups (73 miRNAs were up-regulated, 40 miRNAs were down-regulated). Some of these miRNAs have been previously described in relation to ionizing radiation, and others were herein identified for the first time. We believe that after deeper functional investigation of identified miRNAs in relation to radioresistance, these miRNAs present potential predictive biomarkers or therapeutic targets in GBM.
Keywords: nádory mozku; regulace genové exprese u nádorů; Humans; radioresistance; tolerance záření; Brain Neoplasms; Oligonucleotide Array Sequence Analysis; MicroRNAs; Biomarkers, Tumor; microRNA; Phenotype; lidé; proliferace buněk; glioblastom; apoptóza; nádorové biomarkery; fenotyp; Cell Proliferation; prognóza; stanovení celkové genové exprese; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; nádorové buněčné linie; Glioblastoma; Prognosis; mikro RNA; Radiation Tolerance; Cell Line, Tumor; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Apoptosis